2011
DOI: 10.1371/journal.pone.0028096
|View full text |Cite
|
Sign up to set email alerts
|

Development and Inter-Rater Reliability of the Liverpool Adverse Drug Reaction Causality Assessment Tool

Abstract: AimTo develop and test a new adverse drug reaction (ADR) causality assessment tool (CAT).MethodsA comparison between seven assessors of a new CAT, formulated by an expert focus group, compared with the Naranjo CAT in 80 cases from a prospective observational study and 37 published ADR case reports (819 causality assessments in total).Main Outcome Measures Utilisation of causality categories, measure of disagreements, inter-rater reliability (IRR).ResultsThe Liverpool ADR CAT, using 40 cases from an observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
199
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(225 citation statements)
references
References 21 publications
5
199
1
3
Order By: Relevance
“…We found that families' accounts of how they linked symptoms to a medicine resembled the logic that underpins tools for assessing ADRs 53,188 in research and clinical practice. Participants noted temporal associations between a medicine's administration and the onset of symptoms, the receding of symptoms between doses and the absence of alternative explanations for symptoms.…”
Section: Perspectives On Communication About Adverse Drug Reactionsmentioning
confidence: 86%
See 2 more Smart Citations
“…We found that families' accounts of how they linked symptoms to a medicine resembled the logic that underpins tools for assessing ADRs 53,188 in research and clinical practice. Participants noted temporal associations between a medicine's administration and the onset of symptoms, the receding of symptoms between doses and the absence of alternative explanations for symptoms.…”
Section: Perspectives On Communication About Adverse Drug Reactionsmentioning
confidence: 86%
“…53 Three investigators (RMG, JRB, KAB) independently assessed causality for all possible ADR cases. Agreement on causality category between all three investigators was taken as accepted consensus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Desta forma, apesar do algoritmo ser o indicado pela Organização Mundial de Saúde (OMS) para as análises de causalidade, seu uso em oncologia apresenta importantes limitações. Recentemente, outra ferramenta para analisar causalidade de RAM vem sendo utilizada, parecendo ser mais adequada para pacientes oncológicos [41][42][43] , porém, até o momento, o mesmo ainda não está validado para uso no Brasil.…”
Section: Discussionunclassified
“…The remainder of this article attempts to suggest a research agenda for the future of psychiatry. The recommendations for practicing clinicians are described in Table 5 (59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71).…”
Section: Learning From the Pastmentioning
confidence: 99%